2017
DOI: 10.1371/journal.ppat.1006662
|View full text |Cite
|
Sign up to set email alerts
|

Rice stripe virus NS3 protein regulates primary miRNA processing through association with the miRNA biogenesis factor OsDRB1 and facilitates virus infection in rice

Abstract: MicroRNAs (miRNAs) are small regulatory RNAs processed from primary miRNA transcripts, and plant miRNAs play important roles in plant growth, development, and response to infection by microbes. Microbial infections broadly alter miRNA biogenesis, but the underlying mechanisms remain poorly understood. In this study, we report that the Rice stripe virus (RSV)-encoded nonstructural protein 3 (NS3) interacts with OsDRB1, an indispensable component of the rice (Oryza sativa) miRNA-processing complex. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 67 publications
(74 reference statements)
1
39
0
6
Order By: Relevance
“…After invasion of host cells, some virus-encoded proteins are used to regulate the host's environment, thus helping to increase virus replication (50)(51)(52)(53).Previous studies have revealed that the nsp1 proteins of coronaviruses can regulate the host protein synthesis and help the virus escape the host's immune interference (25,27,43,45,54). The highly variable sequence homology of the coronavirus nsp1 proteins may lead to the diverse mechanisms for inhibiting the host gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…After invasion of host cells, some virus-encoded proteins are used to regulate the host's environment, thus helping to increase virus replication (50)(51)(52)(53).Previous studies have revealed that the nsp1 proteins of coronaviruses can regulate the host protein synthesis and help the virus escape the host's immune interference (25,27,43,45,54). The highly variable sequence homology of the coronavirus nsp1 proteins may lead to the diverse mechanisms for inhibiting the host gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…这些研究揭示了植物与昆虫互作的分子机制, 为农作物抗虫育种提供了重要理论依据与新颖的 思路. [257] ; 近期, 通过与福建农林科技大学的团队合作发 现, 水稻miR528的转录受Squamosa promoter binding protein(SPL)转录因子家族的SPL9调控, 病毒侵染后通 过抑制SPL9的蛋白水平下调miR528前体的转录表 达 [258] ; 通过与美国华人学者合作发现了病毒感染后除 了病毒-特异的siRNA(short interfering RNA), 还大量 积累靶向内源基因的siRNA, 其机制独立于其他内源 小RNA [253] , 提示存在尚不为人知的抗病机制. 此外, 福建农林科技大学与北京大学联合研究组揭示了 miR319参与调控水稻锯齿叶矮缩病毒(rice ragged stunt virus, RRSV)的致病机制 [255] .…”
Section: 华南农业大学研究组与国外科学家合作发现 线虫分 泌的效应蛋白Mjttl5靶向铁氧还原蛋白催化亚基unclassified
“…In the last two decades several mechanisms involved in viral pathogenesis have been revealed in rice plants (Zhang et al 2012;Kong et al 2014;Rong et al 2014;Zhang et al 2016;Zhao et al 2017). In some cases, a single viral protein can be the main responsible agent of the pathogenesis process (Kong et al 2014;Rong et al 2014), while in other cases, several interactions between virus and host factors are needed (Zhu et al 2005;Jin et al 2016;Shi et al 2016;Zhang et al 2016;Tong et al 2017;Zhao et al 2017;Zheng et al 2017) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%